Enhancing Organizational Memory Through Virtual Memoryscapes: Does It Work? - Mastrogiorgio, Antonio; Zaninotto, Francesca; Maggi, Francesca; Ricciardi, Emiliano; Lattanzi, Nicola; Malizia, Andrea P. (Frontiers in Psychology, 2021)
Massive offloading of organizational knowledge onto information systems is often maladaptive, generating digital amnesia. How to enhance cognitive memory through virtual reality represents an issue emerging in translational cognitive neuroscience research, which has never been investigated in organizational settings. We analyze the efficacy of a virtual memoryscape — an immersive virtual environment used by subjects as a shared memory tool based on spatial navigation — with respect to a traditional individual-specific mnemonic method (the well-known ‘method of loci’). A memory task characterized by high ecological validity was administered to 82 subjects with responsibilities in a business unit of a large banking group. Results suggest that enhancing memory through virtual memoryscape is an effective way to counterbalance the maladaptive consequences of massive offloading of information in organizations. As compared to traditional methods, the virtual memoryscape presents the advantages of being collective, controllable, dynamic, and non-manipulable.